PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KEPUASAN KERJA MELALUI LEADER-MEMBER EXCHANGE DI BPJS KETENAGAKERJAAN YOGYAKARTA - Ignatius Soni Kurniawan; Weny Farisca (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2021)
This study aims to determine the role of leader-member exchange as a mediator on the effect of perceived organizational support on job satisfaction. The population in this study were employees of BPJS Ketenagakerjaan Yogyakarta. The sampling technique used a saturated sample. Data were collected using a survey questionnaire and processed using multiple linear regression analysis and Sobel test. The findings show that perceived organizational support affects job satisfaction through leader-member exchange. Organizational leaders can encourage an increase in perceived organizational support to increase leader-member exchange which in turn also strengthens job satisfaction.